مفهوم المصيبة عند علي مصطفى يعقوب وعلاقته في مواجهة جائحة كورونا - Zainal Hamdi; Fatihunnada Fatihunnada (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
This research aims to know the concept of calamity according to Ali Mustafa Yaqoub. The world is currently witnessing a calamity, an epidemic called the Corona virus or COVID-19. In this case of great calamity, people need the right guidance. The researcher took the analytical method by revealing Ali Mustafa Yaqoub’s inference about the calamity that occurred in Aceh, which is the tsunami. The importance of the results that the researcher obtained by searching for is that Ali Mustafa's position in the Corona pandemic. If this COVID-19 pandemic occurs in his life, he will say that this calamity is either as a test of faith, or to promote faith, or as evidence of God’s love for his servants, or as a warning and warning only, not as God’s punishment in this world. People are calling for social distancing, wearing a mask, staying at home, and tightening hygiene by washing hands and using hand sanitizer. He will agree and support decisions from the government to combat the Covid-19 pandemic, even if it is a long and varied journey. He will also call on the community to save the soul with a vaccine immediately. The appellant judges any of the martyrs who were affected by the Corona pandemic.